Prevalence of Salmonella spp. in chicken meat and its products, and development of PCR-ELISA for detection of Salmonella enteritidis - Abdul Talib, Mohd Afendy (2017)
The increase in Salmonella infections necessitate the development of methods for the pathogen detection. Conventional culture for Salmonella detection is laborious and time-consuming. This has encourage the use of Polymerase Chain Reaction (PCR) and PCR-enzyme-linked immunosorbent assay (ELISA) that offer faster result and better sensitivity. To date, there was no published data on the prevalence and quantities of Salmonella spp., S. Enteritidis and S. Typhimurium in raw, processed and ready-to-eat (RTE) chicken samples by most probable number (MPN)-mPCR & MPN-plating and no published data on the effect of two different matrices of raw chicken meat and chicken sausages towards PCR-ELISA performance. Thus, this study is aimed to discover these gaps. The multiplex polymerase chain reaction (mPCR) method was established. Three primer sets were successfully designed to simultaneously identify Salmonella spp., S. Enteritidis and S. Typhimurium. The mPCR containing S. Typhimurium generated 650 bp and 500 bp amplicons, S. Enteritidis generated 500 bp and 103 bp amplicons and S. Typhi produced a 500 bp amplicon. Subsequently, MPN-mPCR was used to determine the prevalence and quantity of Salmonella spp., S. Typhimurium and S. Enteritidis in 130 samples of chicken meat and its products. The prevalence of Salmonella spp., S. Enteritidis and S. Typhimurium obtained is 25.38%, 10% and 6.92% respectively. The prevalence of Salmonella spp. in raw chicken meat was the highest at 45% followed by RTE food at 30% while S. Enteritidis is 22.5% and 8% respectively. No contamination was detected in processed chicken meat products. The estimated quantity of Salmonella spp., S. Enteritidis and S. Typhimurium varied from 3 MPN/g to the 1100 MPN/g. Quantity of Salmonella spp. was found highest in chicken breast and thigh (1100 MPN/g), S. Typhimurium was highest detected in RTE chicken curry (210 MPN/g), while S. Enteritidis was highest detected in chicken breast (93 MPN/g). In subsequent chapter, PCR-ELISA was successfully established and compared with PCR to detect S. Enteritidis in raw chicken meat & chicken sausages. The limit of detection (LOD) by PCR-ELISA is 9.4 CFU/mL in raw chicken meat and 2.46 CFU/mL in chicken sausage while PCR detected 9.4 X 101 CFU/mL and 2.46 X 101 CFU/mL respectively, indicating that the PCRELISA is 10-fold more sensitive than the conventional PCR. In fact, the LOD of PCR-ELISA calculated by GraphPad Prism is 15.23 CFU/mL for chicken sausage and 3.28 CFU/mL for raw chicken meat. The prevalence and quantity of Salmonella spp., S. Typhimurium and S. Enteritidis in the samples discovered in this study indicated that the contaminated chicken samples posed a risk to consumer as it contained high level of contamination which some exceeded the infectious dose (103 CFU/mL) of Salmonella to human. Meanwhile, PCR-ELISA offer as an alternative and improved assay to the PCR and real-time PCR for detection of S. Enteritidis in semi-quantitative and high-throughput manner. The PCR, MPN-mPCR and PCR-ELISA method established in this study, could be used selectively as a screening tools for surveillance and monitoring of foodborne pathogen contamination so that appropriate actions could be taken by the relevant parties.